Integrating Rationality and Mysticism in Religious Education: An Educational Perspective on Islamic and Indigenous Java-Sundanese Traditions in Indonesia - Susanto, Nanang Hasan; Rahayani, Yayan; Muasomah, Muasomah (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
This study explores the educational perspectives within Islam and the Java-Sundanese Indigenous Religion (Agama Djawa Sunda/ADS), focusing on the interplay between rationality and mysticism. Employing a qualitative approach, this study involves literature reviews on the core beliefs of both religions and in-depth interviews with key figures of ADS. The findings of this study reveal that both Islam and ADS incorporate elements of rationality and mysticism. In ADS, mysticism is reflected in traditional practices such as weddings and circumcisions, while in Islam, mysticism is found among groups such as Salafis and Puritanists, who rely on strict textual interpretations, often leading to radicalism. Conversely, the rational aspect of Islam is reflected in progressive interpretations by Islamic scholars, while ADS rationality is demonstrated through its teachings on nationalism and multiculturalism. The distinction between rationality and mysticism is not clear-cut but rather complementary. This study aims to strengthen the religious education curriculum by introducing different religions and incorporating both rational and mystical aspects a balanced proportion.